The State of Entrepreneurship in Radiography Practice in Nigeria - Okpaleke, Michael Sunday; Nwokorie, Emmanuel Chibuike; Sani, Umar Mohammed (British Journal of Healthcare and Medical Research, 2023)
The entrepreneurial ventures in medical radiography practice in Nigeria has been underdeveloped over the last two decades and there is paucity of data on the current state of affairs. The objective of this study is to assess the current state of clinical entrepreneurship practices in Radio-diagnostic centres in Nigeria. A systematic review of research works conducted by researchers who x- rayed entrepreneurship strides in medical radiography was done. Some relevant literature in academic journals with good impact factors were reviewed and documented. Search terms such as entrepreneurship, radiography, current state were used. Findings were synthesized from appraisal and analysis of literature. Our findings showed that entrepreneurship practices in medical radiography were under- developed and plagued by several problems amongst which are poor leadership skills, lack of well-trained manpower, inadequate power supply, poor maintenance culture, low patronage, high cost of services delivery, lack of local content, low pace of technology transfer, unstable economic conditions, high cost of equipment, cyber-security issues, as well as poor financial support. It is concluded that entrepreneurship ventures and practices in medical radiography services in Nigeria were underutilized and operating sub-optimally. There is need to embrace partnerships, credit financing, outcome-based trainings and the provision of good business policies and economic conditions by the government that will promote the growth of small businesses.